The Role of Neuromanagement and Motivation in Improving Organizational Performance - Kuncoro, Fajar Wirahadi; Ismail, Iriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to identify the relevance of Neuromanagement, motivation, and organizational performance, along with the role of motivation as an intervening variable. The research method used is literature study, which involves collecting and analyzing data from various literature sources that are relevant to the research topic, such as articles, proceedings, books and so on. The research results show that Neuromanagement has significant relevance in increasing individual motivation in the work environment. Neuromanagement can influence motivation by increasing an individual's self-awareness and improving decision-making abilities. High motivation, in turn, acts as an intervening variable that links Neuromanagement and organizational performance. This research provides insight into the importance of understanding Neuromanagement in increasing organizational motivation and performance and proposes further research directions to explore this relationship in a more comprehensive and applicable manner